2004
DOI: 10.1093/alcalc/agh062
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Outlet Density and Violence: A Geospatial Analysis

Abstract: The findings show a clear association between alcohol outlet density and violence, and suggest that the issues of alcohol availability and access are fundamental to the prevention of alcohol-related problems within communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
165
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(177 citation statements)
references
References 19 publications
10
165
1
1
Order By: Relevance
“…[15][16][17] This evidence corresponds with traditional market theories which argue that the increased availability of consumer goods results in greater consumer awareness, presents more purchasing opportunities and leads to higher sales. 18 Consequently, it can be reasoned that greater tobacco retailer density has the potential to encourage higher consumption and higher smoking prevalence.…”
supporting
confidence: 64%
“…[15][16][17] This evidence corresponds with traditional market theories which argue that the increased availability of consumer goods results in greater consumer awareness, presents more purchasing opportunities and leads to higher sales. 18 Consequently, it can be reasoned that greater tobacco retailer density has the potential to encourage higher consumption and higher smoking prevalence.…”
supporting
confidence: 64%
“…14,15 Yet, other studies have found that drug-related crime is a stronger predictor of violence than alcohol outlets. 16,17 A separate consideration is that alcohol outlets are not randomly distributed in communities. The limited amount of research in this area has consistently documented that alcohol outlets tend to be concentrated in minority and lowerincome neighborhoods.…”
Section: Introductionmentioning
confidence: 99%
“…Most research using census blocks has been conducted in larger, denser places like Chicago (Bernasco and Block 2011) or Philadelphia (Groff and Lockwood 2014;Haberman and Ratcliffe 2015). Moreover, past research has used census tracts as units of analysis to examine densities of businesses and violent crimes (e.g., Gruenewald et al 2006;Livingston 2008;Zhu et al 2004). …”
Section: Units Of Analysismentioning
confidence: 99%